Experimental investigations of mineral and ester-based oils at low temperature - Anđelković, Miloš N; Đorđević, Dragan M (Proceedings, Electrical engineering institute "Nikola Tesla", 2014)
The aim of this study is to create references to mineral oil and recommendations to design rules for ester oil applications. The interest on application of natural and synthetic ester-based fluids in different high voltage power equipment over the last years is increased. Most of the parameters relevant for insulation and cooling of high voltage equipment are studied at room or normal operating temperatures. Nevertheless, this equipment has to keep its functionality over the range of various uncommon conditions. For regions with cold climate an important issue is the behavior at low temperature. Objective of this work was to determine insulation strength of mineral and ester based oil under homogenous field at low temperatures, for different oil states (moisture content between 5% and 25%). At low temperature (-25 °C), tested ester based oil is not solidified, but in very thick aggregate state. At this temperature its insulation strength is still very high, even higher than at room temperature. As soon as ester based oil gets solidified (-35 °C) its insulation strength drops dramatically. Insulation strength of tested ester based oil, at low temperature, when the oil changes its aggregate state, is not dependent on water content.